Who is thirsty for science and for what kind of science? - Pakot, Ágnes (Socio.hu Társadalomtudományi Szemle, 2013)
Geambașu, Réka– Kardon, Béla– Megyesi, Boldizsár– Patakfalvi–Czirják, Ágnes (2013) Thirst for Science? Social conceptions of the research activity, the factors influencing career choices and the social impacts of the Researchers’ Nights.Budapest: HÉTFA Research Institute – RCISD.Available: http://www.rcisd.eu/files/Thirst_for_Science.pdf [downloaded: 2014–01–01]